Analysis of Leadership Style of Women in The Field of Education in TK Aisyiyah Bumiayu Brebes Regency - Khikmaturohmah, Syara (International Conference of Moslem Society, 2019)
This event will be based on research by the large number of women leaders in education, especially in TK Aisyiyah Bumiayu where majority of its leader is a woman rather than a man. The research method used is Descriptive qualitative approach. The subject of research, namely the school TK Aisyiyah in Bumiayu. Date collection techniques acquire date, quality of date collection are also related to the quality of the research instrument made by the researchers. Research results are obtained, namely that a woman can also lead an institution especially in the institution because a woman is the main educators of at least within a family. In TK Aisyiyah Bumiayu is indeed the majority must be led by women because the institution is indeed in desaign to women leaders.